Moisture tension curves of soils of Northeastern Brazil - Oliveira, Luiz Bezerra de; Queiroz, Eliane Nogueira de (Pesquisa Agropecuaria Brasileira, 2014)
A soil-water study was carried out to establish the relationship between the soil moisture content and the soil moisture tension. Three profiles of four different soils of Northeastern Brazil were studied. The soils were classified as Red Yellow Podzolic, "Terra Roxa", Red Yellow Latosol and Red Yellow Podzolic intergrade to Latosol. After wetting, tensions of 1/10, 1/3, 2,5, 10 and 15 atm were applied to samples of each soil horizon. The data show that the point of levelling off of the moisture tension curves occurs at 5 atm in the Red Yellow Podzolic "Terra Roxa" and Red Yellow Latosol, and at 2 atm, in the Red Yellow Podzolic intergrade to Latosol. According to the standards of the Bureau of Reclamation Manual of the U.S. Department of the Interior, the available water capacity is medium in the Red Yellow Podzolic and "Terra Roxa" and low in the Red Yellow Latosol and Red Yellow Podzolic intergrade to Latosol.
Keywords: Soil physics; soil water; latosolic soils; podzolic soils and "Terra Roxa" soils